Factores relativos al entorno, recursos humanos y sistemas de información y gestión en la adopción del cuadro de mando integral en organizaciones portuguesas - Quesado, Patrícia (2014)
In this paper we aim to identify and analyze a set of variables that can potentially influence the adoption of the Balanced Scorecard (BSC) in Portuguese public and private organizations. These variables are related to the environment (perception of environmental uncertainty), with human resources (support of top management) and, information and management systems (strategic map design and establishment of cause-effect relationships between indicators and perspectives of the BSC). Hypotheses were tested using data obtained from a questionnaire sent to 591 publicly-owned organizations and 549 privately-owned organizations in Portugal, with an overall response rate of 31.3%. The results allow us to conclude that the top management commitment, the development of strategy maps and the establishment of cause-effect relationships are factors that are associated with the implementation of the BSC.